Filling the Migrant Rights Gap: Localized Protections of International Economic and Social Rights. (3rd April 2017) - Frey, Barbara; Pardo, Ana Melisa
Abstract : Under international law, economic and social rights should apply equally to noncitizens unless distinctions in their protection are necessary and proportionate to a legitimate state objective. There is no legitimate state objective to deny food, shelter, or healthcare to noncitizens. Despite this, federal and state governments in the United States take no express affirmative responsibility to respect, protect, or fulfill the economic and social rights of undocumented migrants. The authors designate this lacuna in state protection as a "migrant rights gap." Nonstate actors, including churches and nonprofit organizations—often supported by public funding—work informally to fulfill the minimum core economic and social rights of migrants, as shown through a case study of several organizations in the state of Minnesota. These organizations do not see their work with irregular migrants as "human rights work, " nor are their well-intentioned efforts an efficient or fair way to close the migrant rights gap.